Efektivitas Pengelolaan Dana Komite dalam Upaya Mendukung Pembiayaan Pendidikan pada MTs N 1 Banyuwangi - Abdul Rasid; Suwignyo Widagdo; Lia Rachmawati (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
Education plays a vital role in creating quality, competitive human resources, which is a national priority, including in Indonesia. This study focuses on the effectiveness of managing the committee funds at MTsN 1 Banyuwangi to support educational financing that is not fully covered by the state budget (APBN). Using a qualitative approach through interviews, observations, and documentation, the results show that the management of committee funds has been efficient. In 2021-2022, the received funds amounted to IDR 1,357,610,000, with a realization rate of 93.87%. The following year, committee funds amounted to IDR 1,130,600,000, with 100% realization and a surplus of IDR 33,600,000, which was carried over to 2023-2024. In this period, the received funds amounted to IDR 1,351,125,000, with a proposed budget of IDR 2,080,715,000. As of now, the realization stands at 64.93%, and the management is ongoing as the school year has not yet finished. The committee funds play a crucial role in fulfilling the educational financing needs not fully covered by the national budget and contribute to the improvement of educational quality at MTsN 1 Banyuwangi.